Reproducing computational processes in service-based geo-simulation experiments - Zhiyi Zhu; Min Chen; Lingzhi Sun; Zhen Qian; Yuanqing He; Zaiyang Ma; Fengyuan Zhang; Yongning Wen; Songshan Yue; Guonian Lü (International Journal of Applied Earth Observations and Geoinformation, 2023)
Geo-simulation experiments (GSEs) are experiments allowing the simulation and exploration of Earth’s surface (such as hydrological, geomorphological, atmospheric, biological, and social processes and their interactions) with the usage of geo-analysis models (hereafter called ‘models’). Computational processes represent the steps in GSEs where researchers employ these models to analyze data by computer, encompassing a suite of actions carried out by researchers. These processes form the crux of GSEs, as GSEs are ultimately implemented through the execution of computational processes. Recent advancements in computer technology have facilitated sharing models online to promote resource accessibility and environmental dependency rebuilding, the lack of which are two fundamental barriers to reproduction. In particular, the trend of encapsulating models as web services online is gaining traction. While such service-oriented strategies aid in the reproduction of computational processes, they often ignore the association and interaction among researchers’ actions regarding the usage of sequential resources (model-service resources and data resources); documenting these actions can help clarify the exact order and details of resource usage. Inspired by these strategies, this study explores the organization of computational processes, which can be extracted with a collection of action nodes and related logical links (node-link ensembles). The action nodes are the abstraction of the interactions between participant entities and resource elements (i.e., model-service resource elements and data resource elements), while logical links represent the logical relationships between action nodes. In addition, the representation of actions, the formation of documentation, and the reimplementation of documentation are interconnected stages in this approach. Specifically, the accurate representation of actions facilitates the correct performance of these actions; therefore, the operation of actions can be documented in a standard way, which is crucial for the successful reproduction of computational processes based on standardized documentation. A prototype system is designed to demonstrate the feasibility and practicality of the proposed approach. By employing this pragmatic approach, researchers can share their computational processes in a structured and open format, allowing peer scientists to re-execute operations with initial resources and reimplement the initial computational processes of GSEs via the open web.